Software Technologies 9th International Joint Conference, ICSOFT 2014, Vienna, Austria, August 29-31, 2014, Revised Selected Papers - Holzinger, Andreas; Cardoso, Jorge; Cordeiro, José; Libourel, Therese; Maciaszek, Leszek A.; van Sinderen, Marten (Communications in Computer and Information Science, 2015)
This book constitutes the thoroughly refereed proceedings of the 9th International Joint Conference on Software Technologies, ICSOFT 2014, held in Vienna, Austria, in August 2014. The 15 revised full papers and 6 short papers presented were carefully reviewed and selected from 145 submissions. The papers focus on enterprise software technologies; software engineering and systems security; distributed systems; and software project management.